Writing, History, and Power in the Classroom - Thurner, Lance (Radical Teacher, 2021)
Many students experience difficulty with the tensions and disjunctures between their vernacular ways of communication and standardized college English. The history of linguistic standardization in European imperialism, however, provides a pedagogically helpful critical heuristic for examining with students the power relations inherent in college writing instruction. By historicizing the entanglements of language and power, students are empowered to choose how and what they want to learn based on an awareness of their educational situatedness and with the support of a open and reflexive instructor.